2018
DOI: 10.1111/bcp.13756
|View full text |Cite
|
Sign up to set email alerts
|

Scaling beta‐lactam antimicrobial pharmacokinetics from early life to old age

Abstract: Critical illness is associated with greater PK variability than in healthy volunteers. The maturation models presented will be useful for optimizing beta-lactam dosing, although a prospective, age-inclusive study is warranted for external validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 159 publications
1
15
1
Order By: Relevance
“…Their estimated AGE 50 of 86.8 years, however, is significantly higher than what we found for vancomycin (61.6 years). In addition to differences in elimination processes, the different handling of renal function in the study by Lonsdale et al [35] compared with our analysis might explain the different AGE 50 estimates. Indeed, as seen from Table 2, during model building, AGE 50 ranged from 67.4 to 79.8 years depending on the method used to standardise SCR.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Their estimated AGE 50 of 86.8 years, however, is significantly higher than what we found for vancomycin (61.6 years). In addition to differences in elimination processes, the different handling of renal function in the study by Lonsdale et al [35] compared with our analysis might explain the different AGE 50 estimates. Indeed, as seen from Table 2, during model building, AGE 50 ranged from 67.4 to 79.8 years depending on the method used to standardise SCR.…”
Section: Discussioncontrasting
confidence: 50%
“…By extending this standardised model with an additional sigmoidal decline function, we were able to describe the deterioration in vancomycin clearance with age. Recently, Lonsdale et al [35] have used the same methodology to describe beta-lactam antimicrobial pharmacokinetics from early life to old age. Notwithstanding that tubular secretion and/or re-absorption are likely involved in beta-lactam elimination, these authors found a PMA 50 estimate of 49.7 weeks, which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall quality of evidence (QoE) was rated strong (n = 2) or intermediate (n = 3). The beta-lactams benzylpenicillin, intravenous co-amoxiclav, piperacillin-tazobactam, cefotaxime, and meropenem were well described by Lonsdale et al 15 (DES = 7, strong QoE) across the entire age range. Oral co-amoxiclav was simulated according to the model by deVelde et al 48 (DES = 10, intermediate QoE); ampicillin-sulbactam was modeled according to Soto et al 49 (DES = 9, intermediate QoE); ceftriaxone according to Standing et al 36 (DES = 10, intermediate QoE); and ceftazidime by using the model from Li et al 50 (DES = 7, strong QoE).…”
Section: Selected Pk Models For Simulationmentioning
confidence: 72%
“…66 Models that are scalable across the entire pediatric age range are still lacking for many antibiotics. For beta-lactams a recent study by Lonsdale et al 15 developed a maturation function that is able to describe the maturation of the mostly renal clearance mechanisms in beta-lactams from neonates to elderly patients. For other drug classes similar investigations are still missing.…”
Section: Reviewmentioning
confidence: 99%